A rare occurrence of isolated endogenous Escherichia coli panophthalmitis: a case report - Ahmad Fauzi, Nadhirah; Rosli, Abdul Hadi; Jabbari, Aidila Jesmin (Springer Nature, 2023)
Panophthalmitis is a severe ocular condition that can lead to devastating outcomes, such as evisceration, if not promptly treated. It typically originates endogenously, with urinary tract infection being a common primary source of infection. This report describes a rare case of a 61-year-old Malay patient with left eye panophthalmitis. Ocular culture revealed Escherichia coli, while systemic septic workup yielded negative results. Due to the severity of the ocular condition at presentation and the disproportionate level of pain the patient had, an immunocompromised state was suspected and later the diagnosis of diabetes mellitus was confirmed via laboratory investigation. Despite the delay in presentation, which hindered early intervention, the patient’s eyeball was successfully salvaged through a treatment regimen involving three injections of intravitreal antibiotic administered at 48 to 72-hour intervals and a complete course of intravenous antibiotics. This case report highlights the importance of prompt treatment to salvage an eye from evisceration in the case of panophthalmitis.